Arginase induction and activation during ischemia and reperfusion and functional consequences for the heart - Schlüter, Klaus-Dieter; Schulz, Rainer; Schreckenberg, Rolf (Frontiers in Physiology, 2015)
Induction and activation of arginase is among the fastest responses of the heart to ischemic events. Induction of arginase expression and enzyme activation under ischemic conditions shifts arginine consumption from nitric oxide formation (NO) to the formation of ornithine and urea. In the heart such a switch in substrate utilisation reduces the impact of the NO/cGMP-pathway on cardiac function that requires intact electromechanical coupling but at the same time it induces ornithine-dependent pathways such as the polyamine metabolism. Both effects significantly reduce the recovery of heart function during reperfusion and thereby limits the success of reperfusion strategies. In this context, changes in arginine consumption trigger cardiac remodelling in an unfavourable way and increases the risk of arrhythmia, specifically in the initial post-ischemic period in which arginase activity is dominating. However, during the entire ischemic period arginase activation might be a meaningful adaptation that is specifically relevant for reperfusion following prolonged ischemic periods. Therefore, a precise understanding about the underlying mechanism that leads to arginase induction as well as of it’s mechanistic impact on post-ischemic hearts is required for optimizing reperfusion strategies. In this review we will summarize our current understanding of these processes and give an outlook about possible treatment options for the future.